First Simultaneous Observation of a Night Time Medium‐Scale Traveling Ionospheric Disturbance From the Ground and a Magnetospheric Satellite. Issue 9 (9th September 2021) - Kawai, K.; Shiokawa, K.; Otsuka, Y.; Oyama, S.; Kasaba, Y.; Kasahara, Y.; Tsuchiya, F.; Kumamoto, A.; Nakamura, S.; Matsuoka, A.; Imajo, S.; Kazama, Y.; et al.
Abstract: Medium‐scale traveling ionospheric disturbances (MSTIDs) are a phenomenon widely and frequently observed over the ionosphere from high to low latitudes. Night time MSTIDs are caused generally by the polarization electric field in the ionosphere. However, propagation of this polarization electric field to the magnetosphere has not yet been identified. Here, we report the first observation of the polarization electric field and associated density variations of a night time MSTID in the magnetosphere. The MSTID event was observed by an all‐sky airglow imager at Gakona (geographical latitude: 62.39°N, geographical longitude: 214.78°E, magnetic latitude: 63.20°N), Alaska. The Arase satellite passed over the MSTID in the inner magnetosphere at 0530–0800 UT (2030–2300 LT) on November 3, 2018. This MSTID, observed in 630 nm airglow images, was propagating westward with a horizontal wavelength of ∼165 km, a north–south phase front, and a phase velocity of ∼80 m/s. The Arase satellite footprint on the ionosphere crossed the MSTID in the direction nearly perpendicular to the MSTID phase fronts. The electric field and electron density observed by the Arase satellite showed periodic variation associated with the MSTID structure with amplitudes of ∼2 mV/m and ∼150 cm −3, respectively. The electric field variations projected to the ionosphere are mainly in the east‐west direction and are consistent with the direction of the polarization electric field expected from MSTID growth by E  ×  B drift. This observation indicates that the polarization electric field associated with the MSTID in the ionosphere is projected onto the magnetosphere, causing plasma density fluctuations in the magnetosphere. Plain Language Summary: Medium‐scale traveling ionospheric disturbances (MSTIDs) are propagation of electron density fluctuation in the ionospheric F‐layer. MSTIDs are a common phenomenon from high to low latitudes. From simultaneous observations of airglow imagers in both hemispheres, MSTIDs are known to have a mirror structure at magnetic conjugate hemispheres. If an MSTID is generated by ionospheric instabilities, the polarization electric field associated with the MSTID should propagate along the magnetic field lines. In this paper, we report the first simultaneous observation of an MSTID using a ground‐based airglow imager and the Arase satellite in the magnetosphere. The electric field variations and plasma density fluctuations observed by Arase showed periodic variations associated with the MSTID structure. This result indicates that the spatial inhomogeneity of the ionospheric Pedersen conductivity associated with the MSTID yields the polarization electric field in the ionosphere, and that this polarization electric field was projected onto the magnetosphere. Key Points: First simultaneous observation of an medium‐scale traveling ionospheric disturbance (MSTID) using a ground‐based airglow imager and the Arase satellite in the magnetosphere The polarization electric field associated with the MSTID in the ionosphere was projected to the magnetosphere and observed by Arase The electric field and electron density observed by the Arase satellite showed a periodic variation associated with the MSTID structure